Clinical, functional, and laboratory course of children and adolescents with severe asthma after discontinuation of biologics - Ferraro, Valentina Agnese; Castaldo, Raimondo Junior; Alfier, Fiorenza; Amadi, Margherita; Pertoldi, Chiara; Tonazzo, Valentina; Zanconato, Stefania; Carraro, Silvia (Frontiers in Allergy, 2025)
BackgroundAlthough the benefits of biologics in severe asthma are well established, the optimal strategy to discontinue therapy remains controversial.Aimto evaluate clinical, functional, and laboratory course of children and adolescents with severe asthma after biological therapy withdrawal due to sustained good control. Secondary aim was to identify clinical or inflammatory markers predictive of asthma control after discontinuation.Materials and methodsthis retrospective study included patients 6–19 years with severe asthma followed at the University Hospital of Padua in whom a biologic therapy was discontinued after at least 24 months of treatment. Clinical (GINA, CASI, exacerbations), functional (spirometry), inflammatory (FeNO, IgE, eosinophils), pharmacological (ICS dosage), and quality-of-life (PAQLQ) data were collected over a 24-month follow-up.Resultstwenty-three asthmatic patients (34.8% female) were included. 19 treated with Omalizumab, 3 Dupilumab, and 1 Mepolizumab. At withdrawal, all had well-controlled asthma (GINA and CASI 3). Clinical control scores, spirometry, PAQLQ remained stable overtime. No exacerbation increase was observed. One patient resumed biologic therapy. An increase in eosinophil counts was found in patients classified as not fully controlled at 24 months.Conclusionsclinical and functional benefit of biologics may persist for up to 24 months after biologic withdrawal. After biologic discontinuation, most children maintained symptom control and good quality of life, suggesting that biologic therapy may be stopped in appropriately selected cases. At the same time a close follow-up, including assessment of clinical control, functional parameter and biomarkers, is needed to promptly identify signs associated with possible loss of control.